2016
DOI: 10.1080/15384047.2016.1156260
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 is downregulated but not mutated during human esophageal squamous cell carcinogenesis and has tumor stage-specific functions

Abstract: The transcriptional regulator Kr€ uppel-like factor 4 (KLF4) is decreased in human esophageal squamous cell cancer (ESCC), and Klf4 deletion in mice produces squamous cell dysplasia. Nonetheless the mechanisms of KLF4 downregulation in ESCC and the functions of KLF4 during ESCC development and progression are not well understood. Here, we sought to define the regulation of KLF4 and delineate the stage-specific effects of KLF4 in ESCC. We found that KLF4 expression was decreased in human ESCC and in 8 of 9 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Most samples were available as tissue microarrays (TMAs) 67 , 68 containing primary ESCC ( n = 171), carcinoma in situ (CIS; n = 9), IEN ( n = 7), and normal mucosa ( n = 114). Samples with NOTCH1 mutations ( n = 4; E755*, D469Y, R1279D, and D1457G) and wild-type NOTCH1 ( n = 15) were identified by DNA sequencing (SRP072948) 69 . Given the limitation of TMAs to assess intratumoral cancer cell heterogeneity 70 , we examined whole paraffin blocks ( n = 244) by Hematoxylin and Eosin (H&E) staining and IHC, as described below, following preliminary analysis with TMAs.…”
Section: Methodsmentioning
confidence: 99%
“…Most samples were available as tissue microarrays (TMAs) 67 , 68 containing primary ESCC ( n = 171), carcinoma in situ (CIS; n = 9), IEN ( n = 7), and normal mucosa ( n = 114). Samples with NOTCH1 mutations ( n = 4; E755*, D469Y, R1279D, and D1457G) and wild-type NOTCH1 ( n = 15) were identified by DNA sequencing (SRP072948) 69 . Given the limitation of TMAs to assess intratumoral cancer cell heterogeneity 70 , we examined whole paraffin blocks ( n = 244) by Hematoxylin and Eosin (H&E) staining and IHC, as described below, following preliminary analysis with TMAs.…”
Section: Methodsmentioning
confidence: 99%
“…Tango H et al demonstrated that KLF4 was downregulated in anaplastic meningioma compared with low-grade meningiomas, and KLF4 could reduce the invasive ability of anaplastic meningioma stem-like cells (Tang et al, 2017). Yang Y et al found that KLF4 increased with advanced cancer stage and promoted invasion of human esophageal squamous cell cancer cells (Yang and Katz, 2016). A meta-analysis of 2,988 patients showed that low KLF4 expression was related to worse overall survival and disease-free survival in solid tumor (Yu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although KLF4 expression is decreased in early-stage tumors, increased expression is observed in advanced tumors, and restored expression of KLF4 in human ESCC cells is important for tumor metastasis 31 . On the other hand, decreased expression of KLF5 is observed in human ESCC 27, 28, 33 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 97%
“…KLF4 expression is decreased in 8 of 9 human ESCC cell lines 31 . Gene expression profiling of ESCCs shows that decreased KLF4 correlates with reduced expression of keratin 13 ( KRT13 )—an indicator of cell differentiation in ESCC.…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 97%